AKUMULASI TIMBAL (Pb) PADA IKAN WADER MERAH (Puntius bramoides C.V) DI SUNGAI KALIGARANG, KOTA SEMARANG - Rossi Prabowo (Universitas Wahid Hasyim, 2013)
Heavy metal pollution is very harmful to the environment around us, especially to the aquatic environment. Disposal of industrial waste around Garang watershed directly or indirectly cause pollution of heavy metals, especially Pb. Lead is toxic, Bioaccumulative, biomagnifications and carcinogenic. Of the occurrence of heavy metal pollution in the waters Pb Kaligarang. The fish that live and breed in Kaligarang will also accumulate Pb heavy metal. This study aims to identify water quality downstream, middle and upstream of Kaligarang. ,identify pollution of heavy metal Lead (PB) in Kaligarang Lower, Middle and Upper, and identify the accumulation of heavy metals Lead (Pb) in Red Wader fish. The method used was exploratory observational research with quantitative approach which aims to describe the heavy metal content of Pb in red Wader fish in Kaligarang. From research to know that the water quality of the Kaligarang rivers appropriate based environmental parameters such as temperature, Ph, BOD, DO Kaligarang not exceed the quality standards that apply to water quality classification based on class I. The content of heavy metals Pb at Station I (Ungaran), Station 2 (Monument Suharto) and Station 3 (Simongan) still below the maximum limit criteria for water quality standards according the PP . No. 82 Th 2001. Heavy metal accumulation of Pb in fish is known that the levels of heavy metals contained in red wader fish still be well below the standards set both of FDR New Zealand, FAO , and SNI. 7387.2009. Keyword: Accumulate, Lead, Red Wader